Dialogues on infant gut microbiota from a university extension project - Rocha Soares, Isabella; Graziele Thomaz Alves, Beatriz; Gonçalves da Silva Júnior, Luiz Carlos; Larcher de Almeida, Maria Fernanda; de Aquino Paes, Carina; de Castro Farias, Flávia; de Carlos Santana Capelli, Jane (Guará Journal, 2025)
The aim is to describe an experience report presenting the stages of an action developed by the university extension project called Incentive to Complementary Feeding for Infants (IACOL) with the theme intestinal microbiota of infants. The stages include planning, publicizing, carrying out and evaluating the action. The action took place in October 2023 and took place in the form of a virtual meeting, in which a mediator, a member of the IACOL team, interviewed an expert on the subject, providing greater visibility to a subject that is little covered. Eleven members of the IACOL team, known as educators, took part in this study. Out of a total of 188 registrants, 66.5% (n=125) participated (students) in the IACOL Convida edition, with a peak of 76 students during the live broadcast, which lasted 1 hour and 45 minutes, 223 views, 46 likes and 125 interactions in the chat. The edition was considered a great success by the educators, having had the highest number of registrations and students, and the topic was extremely relevant, despite its lack of explanation to both the university public and the population. According to the educators, IACOL Convida was very satisfactory, exceeding the group’s expectations.